Alfonso Giuliani, Crédit, consommation et production dans la pensée de Thorstein Veblen - Alfonso Giuliani (Revue de la Régulation)
Some elements of Veblen’s institutionalism can offer an interesting interpretation of Graziani’s scheme of the Monetary Theory of Production. On the analytical level, this approach which includes consumer behaviour and choices of firms is based on a methodology of ‘macro-foundation of microeconomics’. In the first case, individual consumer choices are deeply influenced by ‘instincts’, or habits, and especially emulation (i.e. leisure class) in opposition with the axiom of rational choice. In the second case, the company is considered as a place of conflicts. Conflicts are embodied in opposition between the will of the ‘technical’ and the goal of businessmen. The technical want to apply the knowledge gained by expanding output (motived by workmanship), while the businessmen want to contract the production to increase prices and profits (predatory instinct). The volume of production and the employment rate depends crucially on the outcome of bargaining within the enterprises. This setting allows us to resolve the ‘paradox of profits’ in two ways: i) considering the steady increase in consumption by rentier, financed by banks (and/or owners of the banks themselves); ii) assuming heterogeneity of firms allow the possibility that the failure of some firms can provide extra monetary profits for the other firms.